Design of device to monitor asthma severity using mainstream technology with medication administration - Mohamad Haikal Mohamad Rosli, 1993- , author 612387 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Project Paper (Sarjana Muda Kejuruteraan (Bio-Perubatan))- Universiti Teknologi Malaysia, 2018